State of urinary continence after radical prostatectomy: 10-year experience in multiple hospitals in Dhaka, Bangladesh (BIRDEM Medical Journal, 2023)
Background: Radical prostatectomy is a recommended treatment method for patients with localized prostate cancer and a long-life expectancy. Post-radical prostatectomy urinary incontinence (PPI) negatively affects the quality of life. The objective of this study was to assess the state of urinary continence after one year of radical retropubic prostatectomy (RRP).Methods: This prospective study was conducted between 2010 and 2020, at the Department of Urology, in BIRDEM General Hospital, Dhaka Community Medical College Hospital and Evercare Hospital, Dhaka, Bangladesh. During these 10 years, we completed 60 RRP and followed up every patient for 1 year.Results: The mean age was 64.5±7 years and the age ranged from 50 to 75 years. The most common clinical stage was T2b and it was 43 (71.7%). Surgical approach was open retropubic in all cases. The mean operative time was 150 minutes and ranged from 120 to 270 minutes. The mean hospital stays of the respondents was 5 days and the mean catheterization period was 2 weeks. Prolong drainage (more than 5 days) was found in 1 (1.7%) case. Thirty-eight (63.33%) patients were continent by 3 months, 15 (25%) patients were continent by 6 months, 4 (6.66%) by 12 months and the rest 3 (5%) were incontinent at the end of 1 year.Conclusion: In our series, most patients achieved continence after 1 year from RRP and only 5% patients were incontinent after 1 year.BIRDEM Med J 2023; 13(3): 130-135